Fine Particulate Matter Exposure Alters Pulmonary Microbiota Composition and Aggravates Pneumococcus-Induced Lung Pathogenesis - Chen, Yu-Wen; Li, Shiao-Wen; Lin, Chia-Der; Huang, Mei-Zi; Lin, Hwai-Jeng; Chin, Chia-Yin; Lai, Yi-Ru; Chiu, Cheng-Hsun; Yang, Chia-Yu; Lai, Chih-Ho (Frontiers in Cell and Developmental Biology, 2020)
Exposure to fine particulate matter (PM) with aerodynamic diameter ≤ 2.5 μm (PM2.5) is closely correlated with respiratory diseases. Microbiota plays a key role in maintaining body homeostasis including regulation of host immune status and metabolism. As reported recently, PM2.5 exposure causes microbiota dysbiosis and thus promoting disease progression. However, whether PM2.5 alters pulmonary microbiota distribution and aggravates bacteria-induced pathogenesis remains unknown. In this study, we used mouse experimental models of PM2.5 exposure combined with Streptococcus pneumonia infection. We characterized the airway microbiota of bronchoalveolar lavage fluid (BALF) by sequencing 16S rRNA V3–V4 amplicon on the Illumina MiSeq platform, followed by a combination of bioinformatics and statistical analyses. Shannon-diversity index, observed ASVs, and Fisher’s diversity index indicated that microbiota richness was significantly decreased in the mice treated with either PM2.5 or pneumococcus when compared with the control group. The genera Streptococcus, Prevotella, Leptotrichia, and Granulicatella were remarkably increased in mice exposed to PM2.5 combined with pneumococcal infection as compared to mice with pneumococcal infection alone. Histopathological examination exhibited that a more pronounced inflammation was present in lungs of mice treated with PM2.5 and pneumococcus than that in mice groups exposed to either PM2.5 or pneumococcal infection alone. Our results demonstrate that PM2.5 alters the microbiota composition, and thereby enhancing susceptibility to pneumococcal infection and exacerbating lung pathogenesis.